Method for in-situ growth of titanium dioxide nanorod crystal layer on surface of titanium dioxide ceramic
By coating titanium powder on the surface of titanium dioxide ceramic and heat treatment, the crystal lattice of the ceramic surface is changed, and the problem of lack of active growth sites on the surface of the ceramic is solved, and the in-situ growth of the titanium dioxide nanorod crystal layer is achieved, improving its performance and range in a variety of application fields.
Patent Information
- Application Number
- CN202411651442.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing hydrothermal synthesis method is difficult to directly grow the titanium dioxide nanorod crystal layer on the surface of titanium dioxide ceramics, mainly due to the lack of active growth sites on the surface of the ceramics and the mismatch of the lattice.
By coating titanium powder on the surface of titanium dioxide ceramic and heat treatment, the lattice distortion on the surface of the ceramic surface is caused. After removing the titanium powder layer, the titanium dioxide nanorod crystal layer is grown in situ on the surface of the ceramic using hydrothermal reaction.
It has achieved the direct in-situ growth of uniform and stable titanium dioxide nanorod crystal layer with high binding strength and large specific surface area on the surface of titanium dioxide ceramics, which has broadened its application in the fields of photocatalysis, seawater desalination, sewage treatment, etc.
Smart Images

Figure CN119591399A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of titanium dioxide materials and relates to a method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of titanium dioxide ceramics. Background Art
[0002] The titanium dioxide nanorod crystal layer with a nano-ordered array structure has broad application prospects in photocatalysis, seawater desalination, sewage treatment and other fields because of its direct electron transmission channel, large specific surface area, good corrosion resistance and antioxidant properties.
[0003] The commonly used methods for preparing titanium dioxide nanorod crystal layers include hydrothermal synthesis, electrospinning, titanium substrate anodization, template method and chemical vapor deposition. Among them, the hydrothermal synthesis method has the advantages of simple process, easy condition control, low cost, no need for templates, and direct in-situ growth.
[0004] The substrate used in the existing hydrothermal synthesis of titanium dioxide nanorod crystal layers is titanium sheet. [1] , Oxidized titanium layer [2] And FTO conductive glass [3] However, the strength and stability of these substrates are not enough, which greatly limits the application field of titanium dioxide nanorod crystal layers. Therefore, it is urgent to find new substrates for preparing titanium dioxide nanorod crystal layers.
[0005] Titanium dioxide ceramics have inherent high strength, high weather resistance and adjustable pore structure as ceramic materials, which means that they have broader application prospects in fields such as seawater desalination and sewage treatment compared to other existing matrix materials. However, the surface of titanium dioxide ceramics lacks active growth sites and does not match the lattice of titanium dioxide nanorod crystal layer, so it is impossible to directly grow titanium dioxide nanorod crystal layer using hydrothermal synthesis.
[0006] References [1]Cai J, Ye J, Chen S, et al.Self-cleaning, broadband and quasi-omnidirectional antireflective structures based on mesocrystalline rutileTiO 2 nanorod arrays[J].Energy&Environmental Science,2012,5(6):7575-7581. [2]Jaffari GH, Hussain T, Iqbal AM, Abbas Y. Formation and crystallization of TiO 2 nanostructures on various surfaces.Acta Crystallogr BStruct Sci Cryst Eng Mater.2022Aug 1;78(Pt 4):593-605.[3]Wu WQ,Lei BX,Rao HS,et al.Hydrothermal Fabrication of Hierarchically Anatase TiO 2 Nanowire arrays on FTO Glass for Dye-sensitized Solar Cells[J].Scientific Reports, 2013,3:1352. Summary of the invention
[0007] In view of the above problems, the present invention provides a method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of titanium dioxide ceramics.
[0008] In one aspect, the present invention provides a method for in-situ growing a titanium dioxide nanorod crystal layer on a titanium dioxide ceramic surface, comprising the following steps: (1) applying titanium powder on the surface of titanium dioxide ceramics, or dispersing titanium powder in a solvent to form a titanium powder dispersion, and then applying it on the surface of titanium dioxide ceramics, and after drying, obtaining a titanium dioxide ceramic with a surface coated with titanium powder; (2) heat treating the titanium dioxide ceramic coated with titanium powder under certain conditions to cause lattice distortion on the surface of the titanium dioxide ceramic; and removing the titanium powder layer after the reaction on the surface of the titanium dioxide ceramic; (3) A titanium dioxide nanorod crystal layer is in situ grown on the surface of the titanium dioxide ceramic with lattice distortion through a hydrothermal reaction.
[0009] The present invention realizes the change of the surface lattice of the titanium dioxide ceramic by coating titanium powder on the surface of the titanium dioxide ceramic and performing heat treatment. After the titanium powder layer falls off naturally, active growth sites for the growth of titanium dioxide nanorods are provided, making it possible to in-situ grow a titanium dioxide nanorod crystal layer on the surface of the titanium dioxide ceramic. Compared with the existing matrix material, the titanium dioxide ceramic has high strength, high weather resistance and an adjustable pore structure, and is more tightly combined with the titanium dioxide nanorod crystal layer in-situ grown on the surface, which is more conducive to broadening its application in the fields of photocatalysis, seawater desalination, sewage treatment, etc.
[0010] Preferably, in step (1), the amount of titanium powder applied to the surface of the titanium dioxide ceramic is 0.0008-0.02 g / cm 2 .
[0011] Preferably, in step (1), the solvent of the titanium powder dispersion is ethanol or deionized water; and the concentration of the titanium powder dispersion is 5 to 15 mol / L.
[0012] Preferably, in step (2), the parameters of the heat treatment include: the heat treatment temperature is 500-1050°C, the holding time is 0.5-8h, the heating rate is 2-10°C / min, and the ambient atmosphere is a vacuum or inert gas atmosphere; preferably, the heat treatment temperature is 800-900°C, the holding time is 0.5-3h, and the ambient atmosphere is a vacuum or inert gas atmosphere.
[0013] Preferably, in step (2), after the heat treatment, the composition of the titanium powder layer after the surface reaction includes: titanium powder and titanium oxide.
[0014] Preferably, in step (3), the hydrothermal reaction comprises: first preparing a mixed solution of tetrabutyl titanate, hydrochloric acid and deionized water, and then placing the titanium dioxide ceramic with lattice distortion on the surface into the mixed solution and performing a hydrothermal reaction in a hydrothermal reactor to obtain a titanium dioxide nanorod crystal layer grown in situ on the surface of the titanium dioxide ceramic.
[0015] Preferably, the temperature of the hydrothermal reaction is 120-180° C., and the time is 4-20 hours.
[0016] Preferably, the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water in the mixed solution is 1:10-30:10-30; The concentration of the hydrochloric acid is 36-38%.
[0017] Preferably, in step (2), the titanium powder layer after the reaction on the surface of the titanium dioxide ceramic is removed by blowing or washing.
[0018] Beneficial effects: (1) Compared with the prior art, the present invention can directly grow a titanium dioxide nanorod crystal layer in situ on the surface of titanium dioxide ceramics. (2) The titanium dioxide nanorod crystal layer prepared by the present invention has an ordered layered array structure, is uniform and stable, has high bonding strength, a large specific surface area, and has excellent corrosion resistance and antioxidant properties, and can be widely used in photocatalysis, seawater desalination, sewage treatment and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1This is the SEM image of the titanium powder layer that has not been removed from the surface after heat treatment and the titanium dioxide ceramic with lattice distortion on the surface (magnification is ×55); Figure 2 This is a physical picture of the titanium powder layer after heat treatment and the titanium dioxide ceramic with lattice distortion on the surface; Figure 3 XRD results of titanium powder raw material and titanium powder layer removed from the surface after heat treatment of titanium dioxide ceramics; Figure 4 (a) and (b) are SEM images of titanium powder raw materials; (c) and (d) are SEM images of the titanium powder layer removed from the surface of titanium dioxide ceramics after heat treatment (magnifications are ×100, ×2000, ×100, and ×2000, respectively); Figure 5 The XRD results of the titanium dioxide ceramic matrix with lattice distortion on the surface after the titanium dioxide ceramic matrix reacts with heat; Figure 6 The SEM images of the titanium dioxide ceramic in Example 1 (a) and the titanium dioxide ceramic after the in-situ growth of the titanium dioxide nanorod crystal layer on the surface for a hydrothermal time of 6 h (b) (magnifications are ×3000 and 5000, respectively); Figure 7 This is a SEM image of the titanium dioxide ceramic after the titanium dioxide nanorod crystal layer was in situ grown on the surface with a hydrothermal time of 13 h in Example 2 (magnification is ×3000); Figure 8 SEM images of the titanium dioxide ceramic (a) in Example 2, the titanium dioxide ceramic with lattice distortion on the surface (b), and the titanium dioxide ceramic after in-situ growth of a titanium dioxide nanorod crystal layer on the surface (c) (all magnifications are ×3000); Fig. 9 SEM images of the titanium dioxide ceramic (a) in Example 3, the titanium dioxide ceramic with lattice distortion on the surface (b), and the titanium dioxide ceramic after in-situ growth of a titanium dioxide nanorod crystal layer on the surface (c) (all magnifications are ×3000); Fig.10 SEM images of the titanium dioxide ceramic (a) in Example 4, the titanium dioxide ceramic with lattice distortion on the surface (b), and the titanium dioxide ceramic after in-situ growth of a titanium dioxide nanorod crystal layer on the surface (c) (all magnifications are ×3000); Fig.11 The SEM images of the titanium dioxide ceramics after the titanium dioxide nanorod crystal layer is in situ grown on the surface in Example 2 (a), Example 3 (b) and Example 4 (c) (magnifications are ×5000, ×4000 and ×8000, respectively); Fig.12This is a SEM image of a titanium dioxide nanorod crystal layer grown using a seed coating method in Comparative Example 1 (magnification is ×1000); Fig.13 This is a SEM image of the titanium dioxide ceramic after the hydrothermal reaction in Comparative Example 2 (magnification is ×4000); Fig.14 This is a SEM image of the titanium dioxide ceramic after the hydrothermal reaction in Comparative Example 3 (magnification is ×4000); Fig.15 This is a SEM image of the titanium dioxide ceramic after the hydrothermal reaction in Comparative Example 4 (magnification is ×4000); Fig.16 These are SEM images of the titanium dioxide ceramics after the hydrothermal reaction in Comparative Example 5 (magnifications are ×2000 and ×6000, respectively). DETAILED DESCRIPTION
[0020] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.
[0021] The present invention adopts a brush coating method or a solvent dispersion method to coat titanium powder on the surface of titanium dioxide ceramics, removes the titanium powder layer after surface reaction after heat treatment, obtains titanium dioxide ceramics with lattice distortion on the surface, and finally grows a titanium dioxide nanorod crystal layer in situ on the surface of the titanium dioxide ceramics through a hydrothermal reaction. Under appropriate hydrothermal conditions, a titanium dioxide nanorod crystal layer with uniform stability, high bonding strength and large specific surface area can be prepared on the surface of titanium dioxide ceramics by the method provided by the present invention. The titanium dioxide nanorod crystal layer prepared by the present invention has good corrosion resistance, oxidation resistance and other properties, and can be widely used in industries such as photocatalysis, seawater desalination, and sewage treatment.
[0022] In the present invention, titanium powder is coated on the surface of titanium dioxide ceramics to 2 The ceramic matrix reacts thermally to change the lattice of the titanium dioxide ceramic surface. Figure 1-2 As shown, under certain heat treatment conditions, the titanium powder reacts with the ceramic matrix, and after the titanium powder layer after the surface reaction falls off naturally, it is found that the titanium powder reacts with the surface of the titanium dioxide ceramic to cause lattice distortion on the surface of the titanium dioxide ceramic, and the lattice distortion can serve as an active growth site for the growth of titanium dioxide nanorods. Under hydrothermal reaction conditions, a titanium dioxide nanorod crystal layer can be grown in situ at the active growth sites on the surface of the titanium dioxide ceramic.
[0023] Specifically, the thermal reaction process between the titanium powder coated on the surface of the titanium dioxide ceramic and the titanium dioxide ceramic matrix is a 2 The lattice loses oxygen, and the titanium powder absorbs TiO during the thermal reaction. 2 After the reaction is completed, the titanium powder layer (including titanium oxide that absorbs oxygen and titanium powder that does not absorb oxygen) is removed from the surface of the titanium dioxide ceramic matrix. 2 The lattice is in an oxygen-deficient state, that is, lattice distortion (or defects) occurs on the surface of the titanium dioxide ceramic matrix. The lattice distortion can serve as an active growth site for the titanium dioxide nanorod crystal layer. 2 Nanorods can start growing from this lattice distortion.
[0024] In the present invention, on the one hand, the active growth sites of the titanium dioxide nanorod crystal layer are obtained by regulating the thermal reaction between titanium powder and the surface of titanium dioxide ceramic. 2 The degree of oxygen deficiency in the lattice is too large, and there are too many lattice defects, which leads to lattice mismatch and the inability of titanium dioxide nanorods to grow; the heat treatment temperature is too low, which makes the TiO 2 The lattice cannot be deficient in oxygen, lattice distortion cannot occur, and it is difficult to obtain active growth sites, and the titanium dioxide nanorod crystal layer cannot grow either. On the other hand, by regulating the conditions of the hydrothermal reaction, a suitable growth environment is provided for the in-situ growth of titanium dioxide nanorods. In this process, if the temperature of the hydrothermal reaction is too low or the time is too short, the chemical driving force for the growth of titanium dioxide nanorods at the active sites will be insufficient, and the titanium dioxide nanorod crystal layer will not grow; if the temperature of the hydrothermal reaction is too high or the time is too long, the chemical driving force will be too strong, and the titanium dioxide nanorods will grow rapidly, resulting in the titanium dioxide ceramic surface being overfilled with titanium dioxide nanorods and being overly dense, causing the in-situ grown nanorod crystals of the titanium dioxide ceramic to lose the morphological characteristics of the nanorods as a whole.
[0025] The following is an exemplary description of the method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of a titanium dioxide ceramic provided by the present invention.
[0026] Preparation of titanium dioxide ceramic matrix. In the present invention, a dry pressing and sintering method can be used (L.Chen, D.Yao, H.Liang, Y.Xia, Y.-P.Zeng, Highly stable TiO 2ceramics for high efficiency and practical solar-driven interfacial evaporation, Solar Energy, 262 (2023) 111848.), freeze drying and sintering methods (L. Ren, Y.-P. Zeng, D. Jiang, Preparation of porous TiO 2 By a novel freeze casting, Ceramics International, 35 (2009) 1267-1270.) to prepare a titanium dioxide ceramic matrix. As an example, the dry pressing and sintering method includes: using TiO with a particle size of 100 to 2000 nm 2 The powder is used as the raw material, and the initial crystal phase is anatase. 40g of titanium dioxide powder is dry pressed under a pressure of 20MPa to form a ceramic green body. Then the ceramic green body is placed in a muffle furnace and sintered at 1000-1250℃ for 0.5-5h with a heating rate of 1-10℃ / min to obtain a titanium dioxide ceramic matrix. The freeze-drying and sintering method is as follows: TiO with a particle size of 100-2000nm is used as the raw material. 2 The powder is the raw material, and the initial crystal phase is anatase. 2 Powder, ammonium polyacrylate and polyvinyl alcohol are mixed in deionized water, wherein ammonium polyacrylate is TiO 2 1% to 2% of the powder mass, polyvinyl alcohol is TiO 2 1% to 6% of the powder mass, deionized water is TiO 2 20% to 80% of the powder mass is ball-milled in a plastic bottle for 24 hours with zirconium oxide balls as the medium to obtain a well-dispersed and stable slurry. The obtained slurry is de-bubbled using a vacuum degassing machine and then poured into a rectangular rubber mold. The rectangular rubber mold filled with the slurry is then placed in a cold room at -80°C. After 10 hours, the completely frozen sample is peeled off from the rectangular rubber mold and quickly transferred to the vacuum chamber of the freeze dryer. The frozen sample is dried under low vacuum conditions for 15 hours. Due to the sublimation of ice crystals, a ceramic embryo is obtained. The ceramic embryo is then sintered in a muffle furnace at 1000-1250°C for 0.5-5 hours, with a heating rate of 1-5°C / min to obtain a titanium dioxide ceramic matrix.
[0027] Titanium powder is applied to the surface of the titanium dioxide ceramic substrate using a brush, or titanium powder is first dispersed in a solvent to form a titanium powder dispersion, which is then applied to the surface of the titanium dioxide ceramic, and then dried to obtain a titanium dioxide ceramic with titanium powder coated on the surface.
[0028] In an optional embodiment, the amount of titanium powder applied to the surface of the titanium dioxide ceramic is 0.0008-0.002 g / cm 2 .
[0029] In an optional embodiment, the solvent of the titanium powder dispersion is ethanol or deionized water; and the concentration of the titanium powder dispersion is 5 to 15 mol / L.
[0030] The titanium dioxide ceramic coated with titanium powder on the surface is heat treated under certain conditions to cause lattice distortion on the surface of the titanium dioxide ceramic; and the titanium powder layer after the reaction on the surface of the titanium dioxide ceramic is removed.
[0031] In an optional embodiment, the heat treatment temperature is 500-1050°C, the heat treatment time is 0.5-8h, the heating rate is 2-10°C / min, and the ambient atmosphere is a vacuum or inert gas atmosphere; preferably, the heat treatment temperature is 800-900°C, the heat treatment time is 0.5-3h, and the ambient atmosphere is a vacuum or inert gas atmosphere.
[0032] In an optional embodiment, after heat treatment, the composition of the titanium powder layer after surface reaction includes: titanium powder and titanium oxide (such as Ti 2 O. Ti 3 O 5 wait).
[0033] A titanium dioxide nanorod crystal layer is in situ grown on the surface of a titanium dioxide ceramic with lattice distortion by a hydrothermal reaction. Specifically, hydrochloric acid with a concentration of 36 to 38% is slowly added to deionized water while stirring, and then tetrabutyl titanate is added while stirring until the solution is clear to obtain a mixed solution; the titanium dioxide ceramic is purged or cleaned to remove the titanium powder remaining on the surface after heat treatment, and then the titanium dioxide ceramic with lattice distortion on the surface is placed in a hydrothermal reactor, and then the mixed solution is poured into the hydrothermal reactor, and finally the reaction is carried out at a temperature of 120 to 180°C for 4 to 20 hours to obtain a titanium dioxide ceramic with a titanium dioxide nanorod crystal layer grown on the surface. Preferably, the temperature of the hydrothermal reaction is 140 to 160°C, and the time of the hydrothermal reaction is 5 to 10 hours.
[0034] In an optional embodiment, the volume ratio of hydrochloric acid to deionized water is 1-2:1-2. The volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water in the mixed solution is 1:10-30:10-30.
[0035] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0036] Example 1
[0037] The method provided in Example 1 for in-situ growing of a titanium dioxide nanorod crystal layer on the surface of a titanium dioxide ceramic comprises the following steps: (1) Using the titanium dioxide ceramic obtained by dry pressing and sintering (sintering temperature of 1200°C, sintering time of 3h, heating rate of 3°C / min) as the matrix material, 0.1g of titanium powder is dispersed in 20mL of anhydrous ethanol to obtain a titanium powder dispersion, and the obtained dispersion is applied to the surface of the titanium dioxide ceramic with a brush. The titanium dioxide ceramic coated with the titanium powder dispersion is dried and heated to 900°C at a heating rate of 10°C / min in a vacuum atmosphere. After keeping the temperature for 2h, it is cooled in the furnace to obtain a titanium dioxide ceramic with a surface coated with titanium powder and heat treated; the titanium powder layer after the surface reaction is removed to obtain a titanium dioxide ceramic with a lattice distortion on the surface; (2) first slowly dropwise adding hydrochloric acid having a concentration of 36% to 38% into deionized water while stirring, then dropwise adding tetrabutyl titanate while stirring, and stirring until the solution becomes clear to obtain a mixed solution; wherein the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water is 1:20:20; (3) The titanium dioxide ceramic with lattice distortion on the surface obtained in step (1) is placed in a hydrothermal reactor, and then the mixed solution obtained in step (2) is poured into a 200 mL hydrothermal reactor (the filling degree is controlled to be about 40%, and the hydrothermal reactor is a sealed high-temperature and high-pressure hydrothermal reactor with a polytetrafluoroethylene lining in the metal shell), and the reactor is heated by an electric blower drying oven and reacted at a temperature of 150° C. for 6 hours; after the reaction is completed, the hydrothermal reactor is cooled to room temperature and opened, the titanium dioxide ceramic is taken out and rinsed with anhydrous ethanol and deionized water for 2 to 3 times, and finally dried at 100° C. to obtain a titanium dioxide ceramic with an in-situ grown titanium dioxide nanorod crystal layer on the surface.
[0038] Example 2
[0039] The method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of a titanium dioxide ceramic provided in this embodiment 2 comprises the following steps: (1) Using the titanium dioxide ceramic obtained by dry pressing and sintering (sintering temperature of 1200°C, sintering time of 3h, heating rate of 3°C / min) as the matrix material, 0.1g of titanium powder is dispersed in 20mL of anhydrous ethanol to obtain a titanium powder dispersion, and the obtained dispersion is applied to the surface of the titanium dioxide ceramic with a brush. The titanium dioxide ceramic coated with the titanium powder dispersion is dried and heated to 900°C at a heating rate of 10°C / min in a vacuum atmosphere. After keeping the temperature for 2h, it is cooled in the furnace to obtain a titanium dioxide ceramic with a surface coated with titanium powder and heat treated; the titanium powder layer after the surface reaction is removed to obtain a titanium dioxide ceramic with a lattice distortion on the surface; (2) first slowly dropwise adding hydrochloric acid having a concentration of 36% to 38% into deionized water while stirring, then dropwise adding tetrabutyl titanate while stirring, and stirring until the solution becomes clear to obtain a mixed solution; wherein the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water is 1:20:20; (3) The titanium dioxide ceramic with lattice distortion on the surface obtained in step (1) is placed in a hydrothermal reactor, and then the mixed solution obtained in step (2) is poured into a 200 mL hydrothermal reactor (the filling degree is controlled to be about 40%, and the hydrothermal reactor is a sealed high-temperature and high-pressure hydrothermal reactor with a polytetrafluoroethylene lining in the metal shell), and the reactor is heated by an electric blower drying oven and reacted at a temperature of 150° C. for 13 hours; after the reaction is completed, the hydrothermal reactor is cooled to room temperature and opened, the titanium dioxide ceramic is taken out and rinsed with anhydrous ethanol and deionized water for 2 to 3 times, and finally dried at 100° C. to obtain a titanium dioxide ceramic with an in-situ grown titanium dioxide nanorod crystal layer on the surface.
[0040] Example 3
[0041] The method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of a titanium dioxide ceramic provided in this embodiment 3 comprises the following steps: (1) Using the titanium dioxide ceramic obtained by dry pressing and sintering (sintering temperature of 1200°C, sintering time of 3h, heating rate of 3°C / min) as the base material, 0.1g of titanium powder is dispersed in 20mL of deionized water to obtain a titanium powder dispersion, and the obtained dispersion is applied to the surface of the titanium dioxide ceramic with a brush. After drying the titanium dioxide ceramic coated with the titanium powder dispersion, the temperature is increased to 900°C at a heating rate of 10°C / min in a vacuum atmosphere, and then cooled with the furnace after keeping the temperature for 1h to obtain a titanium dioxide ceramic with a surface coated with titanium powder and heat treated; the titanium powder layer after the surface reaction is removed to obtain a titanium dioxide ceramic with a lattice distortion on the surface; (2) first slowly dropwise adding hydrochloric acid having a concentration of 36% to 38% into deionized water while stirring, then dropwise adding tetrabutyl titanate while stirring, and stirring until the solution becomes clear to obtain a mixed solution; wherein the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water is 1:30:30; (3) The titanium dioxide ceramic with lattice distortion on the surface obtained in step (1) is placed in a hydrothermal reactor, and then the mixed solution obtained in step (2) is poured into a 200 mL hydrothermal reactor (the filling degree is controlled to be about 40%, and the hydrothermal reactor is a sealed high-temperature and high-pressure hydrothermal reactor with a polytetrafluoroethylene lining in the metal shell), and the reactor is heated by an electric blower drying oven, and reacted at a temperature of 150° C. for 10 hours; after the reaction is completed, the hydrothermal reactor is cooled to room temperature and opened, the titanium dioxide ceramic is taken out and rinsed with anhydrous ethanol and deionized water for 2 to 3 times, and finally dried at 100° C. to obtain a titanium dioxide ceramic with an in-situ growth of a titanium dioxide nanorod crystal layer on the surface.
[0042] Example 4
[0043] The method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of a titanium dioxide ceramic provided in this embodiment 4 comprises the following steps: (1) Using a titanium dioxide ceramic obtained by freeze drying and sintering (wherein the freeze drying temperature is -80°C and the time is 10 hours; the sintering temperature is 1200°C, the sintering time is 3 hours, and the heating rate is 2°C / min) as the matrix material, 0.1g of titanium powder is dispersed in 20mL of deionized water to obtain a titanium powder dispersion, and the obtained dispersion is applied to the surface of the titanium dioxide ceramic with a brush. The titanium dioxide ceramic coated with the titanium powder dispersion is dried and heated to 900°C at a heating rate of 10°C / min in a vacuum atmosphere. After keeping the temperature for 1 hour, the titanium dioxide ceramic is cooled in the furnace to obtain a titanium dioxide ceramic with a surface coated with titanium powder and heat treated; the titanium powder layer after the surface reaction is removed to obtain a titanium dioxide ceramic with a lattice distortion on the surface; (2) first slowly dropwise adding hydrochloric acid having a concentration of 36% to 38% into deionized water while stirring, then dropwise adding tetrabutyl titanate while stirring, and stirring until the solution becomes clear to obtain a mixed solution; wherein the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water is 1:30:30; (3) The titanium dioxide ceramic with lattice distortion on the surface obtained in step (1) is placed in a hydrothermal reactor, and then the mixed solution obtained in step (2) is poured into a 200 mL hydrothermal reactor (the filling degree is controlled to be about 40%, and the hydrothermal reactor is a sealed high-temperature and high-pressure hydrothermal reactor with a polytetrafluoroethylene lining in the metal shell), and the reactor is heated by an electric blower drying oven, and reacted at a temperature of 150° C. for 8 hours; after the reaction is completed, the hydrothermal reactor is cooled to room temperature and opened, the titanium dioxide ceramic is taken out and rinsed with anhydrous ethanol and deionized water for 2 to 3 times, and finally dried at 100° C. to obtain a titanium dioxide ceramic with an in-situ grown titanium dioxide nanorod crystal layer on the surface.
[0044] Figure 1This is a SEM image of the titanium powder layer that has not been removed from the surface after heat treatment and the titanium dioxide ceramic with lattice distortion on the surface. It can be seen from the figure that the titanium powder coated on the surface of the titanium dioxide ceramic remains in a granular state after the thermal reaction with the titanium dioxide ceramic. From a microscopic point of view, it does not adhere to the surface of the titanium dioxide ceramic due to the thermal reaction with the titanium dioxide ceramic.
[0045] Figure 2 The actual picture of the titanium powder layer after heat treatment and the titanium dioxide ceramic with lattice distortion on the surface. It can be seen from the figure that the titanium powder formed a titanium powder layer after the thermal reaction with the titanium dioxide ceramic surface, and the titanium powder layer can be easily separated from the titanium dioxide ceramic surface after the thermal reaction.
[0046] Figure 3 The XRD results of the titanium powder raw material and the titanium powder layer removed from the surface after heat treatment of titanium dioxide ceramics. As can be seen from the figure, the titanium powder raw material shows the XRD diffraction peak of complete titanium metal, but the titanium powder layer removed from the surface not only shows the XRD diffraction peak of titanium metal, but also adds diffraction peaks of various titanium oxides. This shows that during the thermal reaction between the titanium powder and the surface of the titanium dioxide ceramic, the titanium powder absorbs the oxygen in the titanium dioxide and generates various titanium oxides.
[0047] Figure 4 (a) and (b) are SEM images of titanium powder raw materials; (c) and (d) are SEM images of the titanium powder layer removed from the surface of the titanium dioxide ceramic after heat treatment (magnifications are ×100, ×2000, ×100, and ×2000, respectively). As can be seen from the figure, the surface of the titanium powder before the thermal reaction is obviously smooth, while the titanium powder layer after the thermal reaction presents an expanded surface morphology. This shows that during the thermal reaction between the titanium powder and the surface of the titanium dioxide ceramic, the titanium powder absorbs oxygen from the titanium dioxide and generates various titanium oxides. The density of titanium oxide is greater than that of titanium metal, resulting in its volume expansion.
[0048] Figure 5 The XRD results of the titanium dioxide ceramic matrix with lattice distortion on the surface after the titanium dioxide ceramic matrix and the thermal reaction. As can be seen from the figure, before the thermal reaction, the titanium dioxide ceramic matrix showed obvious diffraction peaks of rutile phase titanium dioxide. After the thermal reaction, in addition to the diffraction peaks of rutile phase titanium dioxide, the titanium dioxide ceramic matrix also had diffraction peaks of various titanium oxides, indicating that the titanium dioxide ceramic thermally reacted with the titanium powder, and part of the oxygen in the titanium dioxide lattice on the surface was taken away by the titanium powder, and part of the lattice was distorted to form titanium oxide.
[0049] Figure 6 The SEM image of the titanium dioxide ceramic used as the matrix in Example 1 (a) and the SEM image of the titanium dioxide ceramic after the in-situ growth of a titanium dioxide nanorod crystal layer on the surface for a hydrothermal time of 6 hours (b). Figure 7This is a SEM image of the titanium dioxide ceramic after the surface in-situ growth of titanium dioxide nanorod crystal layer in Example 2 with a hydrothermal time of 13 hours. As can be seen from the figure, TiO 2 nanorods, and with the increase of hydrothermal time, TiO 2 As the nanorods grow, their size also increases.
[0050] Figure 8 The SEM images of the titanium dioxide ceramic (a), the titanium dioxide ceramic with lattice distortion on the surface (b), and the titanium dioxide ceramic with in-situ growth of titanium dioxide nanorod crystal layer on the surface (c) in Example 2. As can be seen from the figure, the titanium dioxide ceramic coated with titanium powder has obvious morphological changes on the surface after heat treatment. The surface of the titanium dioxide ceramic is reduced during the thermal etching process of the titanium powder. 2 Oxygen deficiency occurs in the lattice, and TiO 2 The active growth sites of nanorods, and then after hydrothermal reaction under appropriate conditions, TiO2 grew at the lattice distortion on the ceramic surface. 2 Nanorods.
[0051] Fig. 9 The SEM images of the titanium dioxide ceramic (a), the titanium dioxide ceramic with lattice distortion on the surface (b), and the titanium dioxide ceramic after in-situ growth of titanium dioxide nanorod crystal layer on the surface (c) in Example 3. As can be seen from the figure, in this Example 3, TiO 2 In addition, compared with Example 1, due to the reduction of the hydrothermal time, TiO 2 The size of the nanorods was significantly reduced.
[0052] Fig.10 The SEM images of the titanium dioxide ceramic (a), the titanium dioxide ceramic with lattice distortion on the surface (b), and the titanium dioxide ceramic after in-situ growth of titanium dioxide nanorod crystal layer on the surface (c) in Example 4. As can be seen from the figure, in this Example 4, TiO 2 In addition, compared with Examples 1-3, TiO nanorods can also be grown on the surface of the ceramic substrate prepared by different preparation methods. 2 Nanorods, only in TiO 2 The nanorods vary in size and morphology.
[0053] Fig.11The SEM images of the titanium dioxide ceramic (c) after the titanium dioxide nanorod crystal layer is in situ grown on the surface in Example 2 (a), Example 3 (b) and Example 4 (c) (magnifications are ×5000, ×4000 and ×8000 respectively). It can be seen from the figure that under appropriate conditions, titanium dioxide nanorod crystal layers with an ordered layered array structure, uniform and stable, and large specific surface area can be prepared on the titanium dioxide ceramic substrate prepared by different methods.
[0054] Comparative Example 1
[0055] In this comparative example 1, TiO 2 Seed-grown TiO 2 The nanorod method comprises the following steps: (1) A titanium dioxide ceramic obtained by dry pressing and sintering (sintering temperature of 1200°C, sintering time of 3 h, heating rate of 3°C / min) was used as the matrix material. The matrix material was immersed in tetrabutyl titanate for 10 s and kept in a muffle furnace at 600°C for 3 h to obtain a titanium dioxide ceramic coated with a surface 2 Seeded Titanium Dioxide Ceramics; (2) first slowly dropwise adding hydrochloric acid having a concentration of 36% to 38% into deionized water while stirring, then dropwise adding tetrabutyl titanate while stirring, and stirring until the solution becomes clear to obtain a mixed solution; wherein the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water is 1:20:20; (3) coating the surface obtained in step (1) with TiO 2 The titanium dioxide ceramic with seed crystals is placed in a hydrothermal reactor, and then the mixed solution obtained in step (2) is poured into a 200 mL hydrothermal reactor (the filling degree is controlled to be about 40%, and the hydrothermal reactor is a sealed high-temperature and high-pressure hydrothermal reactor with a polytetrafluoroethylene lining in the metal shell), and the reactor is heated by an electric blast drying oven, and reacted at a temperature of 150° C. for 13 hours; after the reaction is completed, the hydrothermal reactor is cooled to room temperature and opened, the titanium dioxide ceramic is taken out and rinsed with anhydrous ethanol and deionized water for 2 to 3 times, and finally dried at 100° C. to obtain the TiO 2 The seed crystals grow a titanium dioxide ceramic having a titanium dioxide nanorod crystal layer on the surface of the titanium dioxide ceramic.
[0056] Comparative Example 2
[0057] This comparative example 2 provides a method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of a titanium dioxide ceramic substrate under the condition that the heat treatment temperature is too low, comprising the following steps: (1) Using the titanium dioxide ceramic obtained by dry pressing and sintering (sintering temperature of 1200°C, sintering time of 3h, heating rate of 3°C / min) as the base material, 0.1g of titanium powder is dispersed in 20mL of anhydrous ethanol to obtain a titanium powder dispersion, and the obtained dispersion is applied to the surface of the titanium dioxide ceramic with a brush. The titanium dioxide ceramic coated with the titanium powder dispersion is dried and heated to 400°C at a heating rate of 10°C / min in a vacuum atmosphere, kept warm for 2h, and then cooled in the furnace to obtain a titanium dioxide ceramic with a surface coated with titanium powder and heat treated; the titanium powder layer after the surface reaction is removed to obtain a heat-treated titanium dioxide ceramic; (2) first slowly dropwise adding hydrochloric acid having a concentration of 36% to 38% into deionized water while stirring, then dropwise adding tetrabutyl titanate while stirring, and stirring until the solution becomes clear to obtain a mixed solution; wherein the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water is 1:20:20; (3) The heat-treated titanium dioxide ceramic obtained in step (1) is placed in a hydrothermal reactor, and then the mixed solution obtained in step (2) is poured into a 200 mL hydrothermal reactor (the filling degree is controlled to be about 40%, and the hydrothermal reactor is a sealed high-temperature and high-pressure hydrothermal reactor with a polytetrafluoroethylene lining in the metal shell), and the reactor is heated by an electric blower drying oven and reacted at a temperature of 150° C. for 13 hours; after the reaction is completed, the hydrothermal reactor is cooled to room temperature and opened, the titanium dioxide ceramic is taken out and rinsed with anhydrous ethanol and deionized water for 2 to 3 times, and finally dried at 100° C. to obtain a titanium dioxide ceramic without a titanium dioxide nanorod crystal layer on the surface.
[0058] Comparative Example 3
[0059] This comparative example 3 provides a method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of a titanium dioxide ceramic substrate under the condition that the heat treatment temperature is too high, comprising the following steps: (1) Using the titanium dioxide ceramic obtained by dry pressing and sintering (sintering temperature of 1200°C, sintering time of 3h, heating rate of 3°C / min) as the matrix material, 0.1g of titanium powder is dispersed in 20mL of anhydrous ethanol to obtain a titanium powder dispersion, and the obtained dispersion is applied to the surface of the titanium dioxide ceramic with a brush. The titanium dioxide ceramic coated with the titanium powder dispersion is dried and heated to 1200°C at a heating rate of 10°C / min in a vacuum atmosphere. After keeping the temperature for 2h, it is cooled in the furnace to obtain a titanium dioxide ceramic with a surface coated with titanium powder and heat treated; the titanium powder layer after the surface reaction is removed to obtain a titanium dioxide ceramic with a lattice distortion on the surface; (2) first slowly dropwise adding hydrochloric acid having a concentration of 36% to 38% into deionized water while stirring, then dropwise adding tetrabutyl titanate while stirring, and stirring until the solution becomes clear to obtain a mixed solution; wherein the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water is 1:20:20; (3) The titanium dioxide ceramic with lattice distortion on the surface obtained in step (1) is placed in a hydrothermal reactor, and then the mixed solution obtained in step (2) is poured into a 200 mL hydrothermal reactor (the filling degree is controlled to be about 40%, and the hydrothermal reactor is a sealed high-temperature and high-pressure hydrothermal reactor with a polytetrafluoroethylene lining in the metal shell), and the reactor is heated by an electric blower drying oven and reacted at a temperature of 150° C. for 13 hours; after the reaction is completed, the hydrothermal reactor is cooled to room temperature and opened, the titanium dioxide ceramic is taken out and rinsed with anhydrous ethanol and deionized water for 2 to 3 times, and finally dried at 100° C. to obtain a titanium dioxide ceramic without a titanium dioxide nanorod crystal layer on the surface.
[0060] Comparative Example 4
[0061] This comparative example 4 provides a method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of a titanium dioxide ceramic substrate under the condition that the hydrothermal reaction temperature is too low, comprising the following steps: (1) Using the titanium dioxide ceramic obtained by dry pressing and sintering (sintering temperature of 1200°C, sintering time of 3h, heating rate of 3°C / min) as the matrix material, 0.1g of titanium powder is dispersed in 20mL of anhydrous ethanol to obtain a titanium powder dispersion, and the obtained dispersion is applied to the surface of the titanium dioxide ceramic with a brush. The titanium dioxide ceramic coated with the titanium powder dispersion is dried and heated to 900°C at a heating rate of 10°C / min in a vacuum atmosphere. After keeping the temperature for 2h, it is cooled in the furnace to obtain a titanium dioxide ceramic with a surface coated with titanium powder and heat treated; the titanium powder layer after the surface reaction is removed to obtain a titanium dioxide ceramic with a lattice distortion on the surface; (2) first slowly dropwise adding hydrochloric acid having a concentration of 36% to 38% into deionized water while stirring, then dropwise adding tetrabutyl titanate while stirring, and stirring until the solution becomes clear to obtain a mixed solution; wherein the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water is 1:20:20; (3) The titanium dioxide ceramic with lattice distortion on the surface obtained in step (1) is placed in a hydrothermal reactor, and then the mixed solution obtained in step (2) is poured into a 200 mL hydrothermal reactor (the filling degree is controlled to be about 40%, and the hydrothermal reactor is a sealed high-temperature and high-pressure hydrothermal reactor with a polytetrafluoroethylene lining in the metal shell), and the reactor is heated by an electric blower drying oven and reacted at a temperature of 100° C. for 13 hours; after the reaction is completed, the hydrothermal reactor is cooled to room temperature and opened, the titanium dioxide ceramic is taken out and rinsed with anhydrous ethanol and deionized water for 2 to 3 times, and finally dried at 100° C. to obtain a titanium dioxide ceramic without a titanium dioxide nanorod crystal layer on the surface.
[0062] Comparative Example 5
[0063] Comparative Example 5 provides a method for in-situ growing a titanium dioxide nanorod crystal layer on the surface of a titanium dioxide ceramic substrate under the condition that the hydrothermal reaction time is too long, comprising the following steps:
[0064] (1) Using the titanium dioxide ceramic obtained by dry pressing and sintering (sintering temperature of 1200°C, sintering time of 3h, heating rate of 3°C / min) as the matrix material, 0.1g of titanium powder is dispersed in 20mL of anhydrous ethanol to obtain a titanium powder dispersion, and the obtained dispersion is applied to the surface of the titanium dioxide ceramic with a brush. The titanium dioxide ceramic coated with the titanium powder dispersion is dried and heated to 900°C at a heating rate of 10°C / min in a vacuum atmosphere. After keeping the temperature for 2h, it is cooled in the furnace to obtain a titanium dioxide ceramic with a surface coated with titanium powder and heat treated; the titanium powder layer after the surface reaction is removed to obtain a titanium dioxide ceramic with a lattice distortion on the surface; (2) first slowly dropwise adding hydrochloric acid having a concentration of 36% to 38% into deionized water while stirring, then dropwise adding tetrabutyl titanate while stirring, and stirring until the solution becomes clear to obtain a mixed solution; wherein the volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water is 1:20:20; (3) The titanium dioxide ceramic with lattice distortion on the surface obtained in step (1) is placed in a hydrothermal reactor, and then the mixed solution obtained in step (2) is poured into a 200 mL hydrothermal reactor (the filling degree is controlled to be about 40%, and the hydrothermal reactor is a sealed high-temperature and high-pressure hydrothermal reactor with a polytetrafluoroethylene lining in the metal shell), and the reactor is heated by an electric blower drying oven and reacted at a temperature of 150° C. for 19 hours; after the reaction is completed, the hydrothermal reactor is cooled to room temperature and opened, the titanium dioxide ceramic is taken out and rinsed with anhydrous ethanol and deionized water for 2 to 3 times, and finally dried at 100° C. to obtain a titanium dioxide ceramic with an in-situ grown titanium dioxide nanorod crystal layer on the surface.
[0065] Fig.12 This is a SEM image of the titanium dioxide nanorod crystal layer grown using the seed coating method in Comparative Example 1. As can be seen from the figure, due to the TiO 2 The seed crystals are in granular form, and the titanium dioxide nanorods grown by coating them on the surface of the ceramic substrate also present a nanoflower shape, and cannot be grown in situ on the surface of the titanium dioxide ceramic.
[0066] Fig.13 This is a SEM picture of the titanium dioxide ceramic after the hydrothermal reaction in Comparative Example 2. As can be seen from the figure, the heat treatment temperature is too low, which causes the TiO 2 The degree of lattice oxygen deficiency is insufficient, lattice distortion cannot occur, and active growth sites are difficult to obtain, resulting in the inability of titanium dioxide nanorods to grow in situ. The surface of the titanium dioxide ceramic still maintains the morphology after the reaction with titanium powder.
[0067] Fig.14This is a SEM picture of the titanium dioxide ceramic after the hydrothermal reaction in Comparative Example 3. As can be seen from the figure, the heat treatment temperature is too high, which causes the TiO 2 The lattice distortion is too high. Although there are active growth sites, their lattices are similar to those of TiO 2 The lattice difference is too large, resulting in the inability of titanium dioxide nanorods to grow in situ, and the surface of the titanium dioxide ceramic still maintains the morphology after the reaction with titanium powder.
[0068] Fig.15 This is a SEM picture of the titanium dioxide ceramic after the hydrothermal reaction in Comparative Example 4. As can be seen from the figure, the hydrothermal reaction temperature is too low, resulting in insufficient chemical driving force for the growth of titanium dioxide nanorods at the active sites, titanium dioxide nanorods cannot grow in situ, and the surface of the titanium dioxide ceramic still maintains the morphology after the reaction with the titanium powder.
[0069] Fig.16 This is a SEM picture of the titanium dioxide ceramic after the hydrothermal reaction in Comparative Example 5. As can be seen from the figure, the hydrothermal reaction time is too long, resulting in the titanium dioxide nanorods on the surface of the titanium dioxide ceramic being overfilled and overly dense, so that the nanorod crystals grown in situ in the titanium dioxide ceramic lose the morphological characteristics of the nanorods as a whole.
Claims
1. A method for in-situ growth of a titanium dioxide nanorod crystal layer on a titanium dioxide ceramic surface, characterized in that: Includes: includes the following steps: (1) applying titanium powder on the surface of titanium dioxide ceramics, or dispersing titanium powder in a solvent to form a titanium powder dispersion, and then applying it on the surface of titanium dioxide ceramics, and after drying, obtaining a titanium dioxide ceramic with a surface coated with titanium powder; (2) heat treating the titanium dioxide ceramic coated with titanium powder under certain conditions to cause lattice distortion on the surface of the titanium dioxide ceramic; and removing the titanium powder layer after the reaction on the surface of the titanium dioxide ceramic; (3) A titanium dioxide nanorod crystal layer is in situ grown on the surface of the titanium dioxide ceramic with lattice distortion through a hydrothermal reaction.
2. The method according to claim 1, characterized in that In step (1), the amount of titanium powder applied to the surface of the titanium dioxide ceramic is 0.0008-0.02 g / cm 2 .
3. The method according to claim 1 or 2, characterized in that: In step (1), the solvent of the titanium powder dispersion is ethanol or deionized water; and the concentration of the titanium powder dispersion is 5 to 15 mol / L.
4. The method according to any one of claims 1 to 3, characterized in that In step (2), the parameters of the heat treatment include: the heat treatment temperature is 500-1050° C., and the insulation time is 0.5-8 hours; preferably, the heat treatment temperature is 800-900° C., and the insulation time is 0.5-3 hours.
5. The method according to claim 4, characterized in that In step (2), the heat treatment environment atmosphere is a vacuum or inert gas atmosphere.
6. The method according to any one of claims 1 to 5, characterized in that In step (2), after heat treatment, the composition of the titanium powder layer after surface reaction includes: titanium powder and titanium oxide.
7. The method according to any one of claims 1 to 6, characterized in that In step (3), the hydrothermal reaction comprises: first preparing a mixed solution of tetrabutyl titanate, hydrochloric acid and deionized water, and then placing the titanium dioxide ceramic with lattice distortion on the surface into the mixed solution and performing a hydrothermal reaction in a hydrothermal reactor to obtain a titanium dioxide nanorod crystal layer grown in situ on the surface of the titanium dioxide ceramic.
8. The method according to claim 7, characterized in that The temperature of the hydrothermal reaction is 120-180° C. and the time is 4-20 hours.
9. The method according to claim 7 or 8, characterized in that: The volume ratio of tetrabutyl titanate, hydrochloric acid and deionized water in the mixed solution is 1:10-30:10-30; The concentration of the hydrochloric acid is 36-38%.
10. The method according to any one of claims 1 to 9, characterized in that In step (2), the titanium powder layer after the reaction on the surface of the titanium dioxide ceramic is removed by blowing or washing.
Citation Information
Patent Citations
Method for preparing titanium dioxide nano rod array with adjustable size and density on titanium surface
CN101899709A
Hierarchical-assembly-based silicon-titanium dioxide-polypyrrole three-dimensional bionic composite material and application
CN105618153A
Silver nanorod and titanium dioxide composite material as well as preparation method and application thereof
CN107469817A
Preparation method of titanium dioxide nanorod array
CN113135591A
Preparation Method for Vertically Aligned Titanium dioxide Nanorods Mixed Anatase Rutile
KR101334709B1